Study of Structural and Electronic Properties of Doped Arm Chair Single-Walled Carbon Nanotubes. (2016) - Dhiman, Shobhna; Kumar, Ranjan; Dharamvir, Keya
Abstract: Structural and electronic properties of endohedrally doped armchair single-wall carbon nanotubes (SWCNTs) with a chain of six atoms of Ag and Cu have been studied using ab-initio density functional theory. We investigate the binding energy/atom, ionization potential, electron Affinity and Homo-Lumo gap of doped armchair SWNTs from (4, 4) to (6, 6) with two ends open. BE/atom is maximum for (5, 5) doped armchair carbon nanotube; suggest that it is more stable than (4, 4) and (6, 6) doped tubes. Whereas ionization potential of Ag doped tubes is more and electron affinity is less with respect to of Cu doped tubes showing that Ag doped tubes are less reactive than Cu doped tubes. Homo- Lumo gap of doped arm chair tubes decreases exponentially with the increase in diameter of the tubes. This shows that confinement induce a strong effect on electronic properties of doped tubes. These combined systems can be used for future Nano electronics. The ab–initio calculations were performed with SIESTA code using generalized gradient approximation (GGA).